Effect of pea stunt disease on flowering, podding, grain setting and yield - R.N. SINGH, A.T. KHAN and (Indian Phytopathology, 2002)
Field trials were conducted at the University Experiment Station, Masodha, Faizabad, India, during the rabi seasons of 1985-88 using the pea cultivar Rachna. In moderately diseased pea plants, pea stunt incited by red clover vein mosaic carlavirus, caused 70.4, 75, 87.7, 76.7 and 87.8% reduction, respectively, in the number of flowers, pods, grains, percentage normal grains and grain weight per plant. The reduction in these yield components increased progressively with increasing disease severity and reached 100% in the case of severely diseased plants. Except for the number of flowers and pods produced per plant, the differences between healthy and diseased plants and between diseased plants belonging to different disease-severity grades (moderately, heavily and severely diseased) were statistically significant.